2006
DOI: 10.1021/jp0640530
|View full text |Cite
|
Sign up to set email alerts
|

Structural Disorder of the CD3ζ Transmembrane Domain Studied with 2D IR Spectroscopy and Molecular Dynamics Simulations

Abstract: In a recently reported study [Mukherjee, et al. Proc. Natl. Acad. Sci. U.S.A. 2006, 103, 3528], we used 2D IR spectroscopy and 1-13 C═ 18 O isotope labeling to measure the vibrational dynamics of 11 amide I modes in the CD3ζ transmembrane domain. We found that the homogeneous line widths and population relaxation times were all nearly identical, but that the amount of inhomogeneous broadening correlated with the position of the amide group inside the membrane. In this study, we use molecular dynamics simulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
88
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(93 citation statements)
references
References 65 publications
(208 reference statements)
5
88
0
Order By: Relevance
“…In fact, at transmembrane position 9, not only was dimerization abrogated but also the resulting receptor (C2G L9C) was markedly affected with regard to Ag sensitivity, suggesting this residue plays an important functional role in CD3z signaling. Data supporting this theory come from two-dimensional infrared spectroscopic analysis of the CD3z transmembrane domain in which a kink in the dimer at position L9 was identified (32,33). This kink may play a functional role in regulating the structural deformation or twisting/piston-like movement that is predicted to precede TCR signaling events (34)(35)(36).…”
Section: Discussionmentioning
confidence: 96%
“…In fact, at transmembrane position 9, not only was dimerization abrogated but also the resulting receptor (C2G L9C) was markedly affected with regard to Ag sensitivity, suggesting this residue plays an important functional role in CD3z signaling. Data supporting this theory come from two-dimensional infrared spectroscopic analysis of the CD3z transmembrane domain in which a kink in the dimer at position L9 was identified (32,33). This kink may play a functional role in regulating the structural deformation or twisting/piston-like movement that is predicted to precede TCR signaling events (34)(35)(36).…”
Section: Discussionmentioning
confidence: 96%
“…Parametrized electrostatic calculations using the building block approach have been used in protein amide I sim-ulations of ubiquitin, 10,33 other proteins 34 as well as polypeptides in membrane environment. 29,35 These calculations are generally combined with MD simulations that provide coordinate trajectories, which are then utilized for calculating instantaneous normal modes and the resulting spectral line shapes. 36 It has been clearly demonstrated that heterogeneity in the site frequencies needs to be well reproduced in order to obtain agreement with spectra, as shown for ubiquitin by Cho and co-workers.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 At a more subtle level, the helices themselves may bend at hinge regions 3 or exhibit local structural fluctuations involving brief openings of amide hydrogen bonds. 4 Little is currently known about the potential biological significance of these local transmembrane domain (TMD) helix fluctuations. It seems clear, however, that evolutionary fine-tuning can optimize a functional role of helix dynamics if it depends on primary structure.…”
Section: Introductionmentioning
confidence: 99%